Comparing Etymological Characteristics of Plant Naming in Yakut, Even, and Evenk Languages - Osorova, Marina A.; Malysheva, Ninel V.; Timofeeva, Ayta V. (The Arctic Institute of North America, 2022)
This article considers issues of language contacts between Yakut, Even, and Evenk people through an analysis of plant vocabulary. We define etymological characteristics of fixed lexical units that denote plant names and present results of a comparative analysis of plant naming in these three languages, with emphasis on lexical parallels and structural types in designating plant names. To our knowledge, this is the first research to undertake a comparative study of plant naming in the Yakut and Tungusic languages (Even and Evenk) with consideration of the methods of their formation. The study is highly relevant because of the unique contribution of plant-world vocabulary in helping to clarify peculiarities of native speakers’ natural environments. Our results show that, based on lexical units with stable semantic meaning, the Evenk language is in the closest position vis-à-vis Yakut. There are 16 names in Yakut of plants and four of common names of herbs that grow on the territory of the Republic of Sakha (Yakutia) and have borrowed names in Evenk and Even. Twenty-eight names have lexical parallels in Evenk (including variations) and two in Even. Cet article se penche sur la question des contacts linguistiques entre les Yakoutes, les Évènes et les Evenkis au moyen de l’analyse du vocabulaire des plantes. Nous définissons les caractéristiques étymologiques d’unités lexicales fixes dénotant les noms de plantes et présentons les résultats de l’analyse comparative de la nomenclature de plantes dans ces trois langues, en mettant l’accent sur les parallèles lexicaux et les types structuraux de la désignation des noms de plantes. À notre connaissance, il s’agit de la première recherche à entreprendre l’étude comparative de la nomenclature botanique en langues yakoute et toungouse (évène et evenki) tout en tenant compte de leurs méthodes de formation. Cette étude est d’une grande pertinence, car l’apport unique du vocabulaire des plantes aide à expliquer les particularités des milieux naturels des locuteurs natifs. ...